2015
DOI: 10.1371/journal.pone.0135659
|View full text |Cite
|
Sign up to set email alerts
|

Digital Photoplethysmography for Assessment of Arterial Stiffness: Repeatability and Comparison with Applanation Tonometry

Abstract: IntroductionArterial stiffness is an independent risk factor for cardiovascular morbidity and can be assessed by applanation tonometry by measuring pulse wave velocity (PWV) and augmentation index (AIX) by pressure pulse wave analysis (PWA). As an inexpensive and operator independent alternative, photoelectric plethysmography (PPG) has been introduced with analysis of the digital volume pulse wave (DPA) and its second derivatives of wave reflections.ObjectiveThe objective was to investigate the repeatability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 47 publications
1
72
3
5
Order By: Relevance
“…However, this correlation became insignificant after adjustment for the age and MAP (r=0.16). A study by von Wowern et al (2015) found that b/a ratio was correlated significantly with PWV (r=0.56). Compared to above studies, PPGF correlation with PWV was weak (r=-0.27) which suggest that PWV may not be the only marker that influence PPGF.…”
Section: Discussionmentioning
confidence: 98%
“…However, this correlation became insignificant after adjustment for the age and MAP (r=0.16). A study by von Wowern et al (2015) found that b/a ratio was correlated significantly with PWV (r=0.56). Compared to above studies, PPGF correlation with PWV was weak (r=-0.27) which suggest that PWV may not be the only marker that influence PPGF.…”
Section: Discussionmentioning
confidence: 98%
“…An index of arterial stiffness (SI) defined as h/Δt, where h is the height of the experimental subject, is considered a simple index to measure arterial stiffness. [33] Furthermore, the ratio d/b reflects arterial stiffness and decreases with age, that is, the d peak moves downward (Figure 5b-d ii), and ratio d/b becomes more negative with aging ( Figure 5g). In addition, AI could reflect the vascular age, that is, arterial stiffness.…”
Section: Wwwadvelectronicmatdementioning
confidence: 97%
“…The Meridian™ DPA apparatus automatically generates HR and 16 different pulse wave indices of arterial function based on the PPG waveform contour and its second derivative (acceleration PPG, called APG), and can to some extent separate arterial stiffness in central and peripheral vessels (10). The physiological background of PPG contour analysis has previously been described by Millasseau et al (24), and we have described the physiological and mathematical background of DPA variables and validated the Meridian™ DPA indices (11). Based on our previous findings of repeatability and correlation to applanation tonometry variables (11), we chose to restrict the analysis to five DPA indices: cardiac ejection elasticity index (EEI) and b/a for stiffness in central arteries and left ventricular capacity, dicrotic index (DI) and d/a for peripheral arteries, and aging index (AI) for systemic arterial stiffness.…”
Section: Digital Pulse Wave Analysismentioning
confidence: 80%
“…The physiological background of PPG contour analysis has previously been described by Millasseau et al (24), and we have described the physiological and mathematical background of DPA variables and validated the Meridian™ DPA indices (11). Based on our previous findings of repeatability and correlation to applanation tonometry variables (11), we chose to restrict the analysis to five DPA indices: cardiac ejection elasticity index (EEI) and b/a for stiffness in central arteries and left ventricular capacity, dicrotic index (DI) and d/a for peripheral arteries, and aging index (AI) for systemic arterial stiffness. A physiological interpretation of the DPA variables is presented in Table 1.…”
Section: Digital Pulse Wave Analysismentioning
confidence: 81%
See 1 more Smart Citation